2008
DOI: 10.1002/dvdy.21520
|View full text |Cite
|
Sign up to set email alerts
|

FGF signaling segregates biliary cell‐lineage from chick hepatoblasts cooperatively with BMP4 and ECM components in vitro

Abstract: Intrahepatic bile ducts (IHBDs) are indispensable for transporting bile secreted from hepatocytes to the hepatic duct. The biliary epithelial cells (BECs) of the IHBD arise from bipotent hepatoblasts around the portal vein, suggesting the portal mesenchyme is essential for their development. However, except for Notch or Activin/ TGF-␤ signaling molecules, it is not known which molecules regulate IHBD development. Here, we found that FGF receptors and BMP4 are specifically expressed in the developing IHBD and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 66 publications
2
44
0
Order By: Relevance
“…Presumably, it is some aspect of cell-to-cell interaction that is critical for induction of multicellular bile ductule formation by the PICM-19 cells. The feeder-independent culture, therefore, provides an experimental platform from which to investigate what factors may be important in inducing duct formation by PICM-19 cells, such as the interplay of elevated culture pH (Talbot et al 2002), matrix interactions (Yanai et al 2008), and HGF levels (Montesano et al 1991a, b). Without the presence of the feeder cells, the reliance of the PICM-19 cell culture on STO conditioned medium can be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, it is some aspect of cell-to-cell interaction that is critical for induction of multicellular bile ductule formation by the PICM-19 cells. The feeder-independent culture, therefore, provides an experimental platform from which to investigate what factors may be important in inducing duct formation by PICM-19 cells, such as the interplay of elevated culture pH (Talbot et al 2002), matrix interactions (Yanai et al 2008), and HGF levels (Montesano et al 1991a, b). Without the presence of the feeder cells, the reliance of the PICM-19 cell culture on STO conditioned medium can be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Given that hepatic stellate cells also express jagged 1 (66), it will be interesting to investigate whether they modulate biliary cell development via Notch signaling. Alternatively, hepatic stellate cells could influence hepatoblast differentiation through production of ECM proteins, as different ECM components have different effects on the determination of the hepatocyte and biliary cell fate (67,68).…”
Section: Hepatic Stellate Cells In Liver Developmentmentioning
confidence: 99%
“…Several FGFR2b ligands are implicated in developing livers, including FGF1, FGF7, and FGF10. In vitro studies have shown that FGF1 enriches bipotential hepatic progenitor cells, whereas FGF7 promotes differentiation of biliary epithelial cells (BECs) in cultured embryonic livers [5,6]. Expression of FGF10 in hepatic stellate cells (HSCs) is crucial for the developing liver by maintaining survival of hepatoblasts through FGFR2b receptor [4].…”
Section: Introductionmentioning
confidence: 99%